WILD PLANTS AS AN OBJECT OF STUDY, LIFE SAFETY, USE IN MEDICINE AND INDUSTRY (Modern education and development, 2025)
The flora of Uzbekistan is extremely rich and diverse. Deserts and steppes, mountains and foothills, plains and river deltas coexist side by side and form an amazing landscape. This may seem incredible, but in reality, compared with the neighboring regions of Central Asia, the number of plants per unit area in the foothills and mountainous regions of Uzbekistan is many times higher.About 80% of them are naturally growing plants, but in recent years large areas of artificial plantations have been increasingly appearing. According to the World Health Organization, 60% of medicines used in modern medicine are prepared and produced on the basis of medicinal plant raw materials.